A Novel Poly(3, 4-ethylenedioxythiophene)-graphene Oxide/Titanium Dioxide Composites Counter Electrode for Dye-Sensitized Solar Cell. (12th October 2017) - Mustafa, Muhammad Norhaffis; Shafie, Suhaidi; Zainal, Zulkarnain; Sulaiman, Yusran
Abstract : PEDOT-based material counter electrodes (CEs) are recently given an enormous attention as new renewable energy sources due to their cost-effectiveness and accessibility, coupled with the simplicity of production. The existing dye-sensitized solar cells (DSSCs) are expensive because they are made using platinum-based glass electrode. In this work, a new CE, that is, poly(3, 4-ethylenedioxythiophene)-graphene oxide/titanium dioxide (PEDOT-GO/TiO2 ) with a low charge transfer resistance (R c t = 9.0  Ω), was fabricated. In addition, PEDOT-GO/TiO2 CE possesses a good electrocatalytic activity (ECA) toward the tri-iodide ions reduction and an improved efficiency of 1.166% was reached in DSSC.